Intergrating technology in English language arts teacher education - Pasternak, Donna L.; Routledge (Firm) (New York: Routledge, Taylor & Francis Group, 2020)
"Integrating Technology in English Language Arts Teacher Education investigates the technology practices which teacher candidates in the US are being introduced to, how they are using these practices in classrooms, and how technology can be effectively integrated into English teacher education programs. By drawing upon findings from extensive longitudinal studies into teacher education programs in the US, this timely volume addresses critical themes relating to the integration of technology in education, including: Teaching with technology, Technology for collaboration, Technology for individualized learning and assessment. By analyzing the experiences of teacher educators and candidates, and offering detailed analysis of the content, practices, and skills being taught to pre-service English teachers, Pasternak examines the entities that drive or inhibit the adoption of technology into the secondary ELA curriculum. This volume will resonate with an international audience of post-graduate scholars and researchers interested in the fields of teacher education, English Language Arts, and the relationship between technology and classroom practice"--
Includes appendix and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Language and languages -- Study and teaching -- Technological innovations; Language and languages -- Study and teaching -- Data processing; Web-based instruction; Curriculum planning -- Technological innovations